2005
DOI: 10.1002/hipo.20065
|View full text |Cite
|
Sign up to set email alerts
|

Effect of prenatal protein malnutrition on numbers of neurons in the principal cell layers of the adult rat hippocampal formation

Abstract: Malnutrition has been associated with a variety of functional and anatomical impairments of the hippocampal formation. One of the more striking of these is widespread loss of hippocampal neurons in postnatally malnourished rats. In the present study we have investigated the effect of prenatal malnutrition on these same neuronal populations, neurons that are all generated during the period of the dietary restriction. In prenatally protein deprived rats, using design-based stereology, we have measured the region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
87
1
10

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(108 citation statements)
references
References 54 publications
6
87
1
10
Order By: Relevance
“…In mammals, this process takes place in the CA1 region of the hippocampus, and the underlying cellular mechanism is a form of synaptic plasticity known as long‐term potentiation or LTP (Vann & Albasser, 2011), that requires Ca +2 signaling, gene expression changes and protein synthesis (Morgado‐Bernal, 2011). The neuropathological bases of learning and memory alterations in IUGR babies are not clear, but there is consensus that within the brain the hippocampus is one of the areas most susceptible to IUGR and hypoxic damage (Fung et al., 2012; Lodygensky et al., 2008; Mallard et al., 2000), which particularly affects CA1 pyramidal neurons in the hippocampus (Kovalenko et al., 2006; Lister et al., 2005). In this study, the ischemic and IUGR CMO groups presented a reduction in CA1 neuronal number, mild gliosis and paradoxical changes in PSD95 and synaptophysin expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, this process takes place in the CA1 region of the hippocampus, and the underlying cellular mechanism is a form of synaptic plasticity known as long‐term potentiation or LTP (Vann & Albasser, 2011), that requires Ca +2 signaling, gene expression changes and protein synthesis (Morgado‐Bernal, 2011). The neuropathological bases of learning and memory alterations in IUGR babies are not clear, but there is consensus that within the brain the hippocampus is one of the areas most susceptible to IUGR and hypoxic damage (Fung et al., 2012; Lodygensky et al., 2008; Mallard et al., 2000), which particularly affects CA1 pyramidal neurons in the hippocampus (Kovalenko et al., 2006; Lister et al., 2005). In this study, the ischemic and IUGR CMO groups presented a reduction in CA1 neuronal number, mild gliosis and paradoxical changes in PSD95 and synaptophysin expression.…”
Section: Discussionmentioning
confidence: 99%
“…In the same line, neuroimaging and histopathological studies of the IUGR brain in infants and animal models have shown that one of the areas most affected is the hippocampus (Dieni & Rees, 2003; Lister et al., 2005; Lodygensky et al., 2008). The hippocampus is a structure involved in codification, storage, and recovery mechanisms related to learning and memory processes (Vann & Albasser, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Malnutrition also affects structures involved in learning and memory processes, including the hippocampus and hypothalamus [2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Bold Responsementioning
confidence: 99%
“…Studies of malnourished animal models, using postmortem histological and imaging analyses, have revealed a range of morphological changes, including a decrease in the prenatal brain size [2], a decrease in the postnatal brain size [3], fewer hippocampal neurons [4], diminished granular volume of cortex [5], abnormalities in the dendritic spines of the cerebellar cortex [6], reduced myelin content [7], and reduced synthesis of myelin-associated proteins [8].…”
Section: Introductionmentioning
confidence: 99%
“…No sistema nervoso central (SNC), a elevação de corticosterona mediada pelo estresse contribui para a atrofia hipocampal, mas não é suficiente para causar morte neuronal (Lister et al, 2005;Kehoe, et al 2001;Mesquita, et al 2003e Schertel et al 1991.…”
Section: Introductionunclassified